MERGERS IN HIGHER EDUCATION FOR SUSTAINABLE DEVELOPMENT: A SYSTEMATIC LITERATUR REVIEW - Ardie Putra, Alfian Prayana; Khairusy, Mirza Abdi; Prameswari, Yuda Nabella; Atmaja, Sukarta (LPPM Universitas Banten jaya, 2025)
This paper discusses sustainable development issues in the higher education sector from the higher education perspective. Higher Education Institutions (HEIs) are important actors in achieving the Sustainable Development Goals (SDGs) and the 2030 Agenda set by the United Nations General Assembly in 2015. This paper aims to conceptualize impacts of higher education institutions (HEIs) on sustainable development (SD), This review aims to provide the available constructive literature on merger higher education with a theoretical and empirical background published during the past 5 years, from January 2019- November 2024, to identify impack merger higher education to sustnaible development and factors marger higher education. The author searched for articles in two databases(Scopus and Proquest). The contribution of this research becomes a reference in understanding impack merger higher education to sustnaible development and determining the factors of merger in higher education.